Analysis of Factors Affecting Athlete Achievement in Sports Competitions - Laoli, Teni Anugerah; Prawiro, Triantomo Harjo; Pratama, Tio Wahyu; Sari, Vivi Dwita; Wahidin, Taufan Arif; Sirait, Wahyu Alexandrian; Butar, Vivi Inriani Butar; Barus, Tomi Andrianus; Devalda, Hessa Novila (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2025)
Objective. This study aims to analyze the factors that influence athlete performance in sports competitions. Materials and Methods. This study uses quantitative methods with data collection techniques through questionnaires and interviews. The population of the study were athletes participating in national sports competitions, with a sample of 100 athletes selected randomly. Results. The results of the study showed that the factors that influence athlete performance in sports competitions include physical factors (strength, speed, endurance, flexibility), psychological factors (motivation, concentration, self-confidence), technical factors (technical ability, strategy, tactics), and environmental factors (field conditions, weather, support from coaches and teams). Conclusion. Athletes’ performance in sports competitions is influenced by various factors that can be categorized into physical, psychological, technical, and environmental factors. Therefore, coaches and athletes must pay attention to these factors to improve performance in competitions. This study recommends that training programs should be designed comprehensively by considering physical, psychological, technical, and environmental aspects. In addition, further research is recommended to explore the interactions between these factors in more depth and develop more specific strategies to improve athlete performance sustainably.